Does Spine Surgery in Patients with a History of Bariatric Gastrectomy Increase the Risk of Delayed Pulmonary Embolism? - Mohammad Zarei; Mohsen Rostami; Furqan Mohammed Yaseen Khan (Journal of Orthopedic and Spine Trauma, 2022)
Background: This is a novel observation report on patients undergoing spine surgery with a history of bariatric procedures.